Sea‐air CO2 exchange in the western Arctic coastal ocean. Issue 8 (14th August 2015) - Evans, Wiley; Mathis, Jeremy T.; Cross, Jessica N.; Bates, Nicholas R.; Frey, Karen E.; Else, Brent G. T.; Papkyriakou, Tim N.; DeGrandpre, Mike D.; Islam, Fakhrul; Cai, Wei‐Jun; Chen, Baoshan; Yamamoto‐Kawai, Michiyo; et al.
Abstract: The biogeochemical seascape of the western Arctic coastal ocean is in rapid transition. Changes in sea ice cover will be accompanied by alterations in sea‐air carbon dioxide (CO2 ) exchange, of which the latter has been difficult to constrain owing to sparse temporal and spatial data sets. Previous assessments of sea‐air CO2 flux have targeted specific subregional areas of the western Arctic coastal ocean. Here a holistic approach is taken to determine the net sea‐air CO2 flux over this broad region. We compiled and analyzed an extensive data set of nearly 600, 000 surface seawater CO2 partial pressure ( p CO2 ) measurements spanning 2003 through 2014. Using space‐time colocated, reconstructed atmospheric p CO2 values coupled with the seawater p CO2 data set, monthly climatologies of sea‐air p CO2 differences (Δ p CO2 ) were created on a 0.2° latitude × 0.5° longitude grid. Sea‐air CO2 fluxes were computed using the Δ p CO2 grid and gas transfer rates calculated from climatology of wind speed second moments. Fluxes were calculated with and without the presence of sea ice, treating sea ice as an imperfect barrier to gas exchange. This allowed for carbon uptake by the western Arctic coastal ocean to be assessed under existing and reduced sea ice cover conditions, in which carbon uptake increased 30% over the current 10.9 ± 5.7 Tg C (1 Tg = 10 12  g) yr −1 of sea ice‐adjusted exchange in the region. This assessment extends beyond previous subregional estimates in the region in an all‐inclusive manner and points to key unresolved aspects that must be targeted by future research. Key Points: An extensive data set of western Arctic coastal ocean seawater p CO2 was analyzed Sea ice‐adjusted annual carbon uptake was 5% of global coastal ocean exchange Areas of uncertainty were used to pinpoint next steps for future research